2017
DOI: 10.1038/cddiscovery.2016.106
|View full text |Cite
|
Sign up to set email alerts
|

TFF3-dependent resistance of human colorectal adenocarcinoma cells HT-29/B6 to apoptosis is mediated by miR-491-5p regulation of lncRNA PRINS

Abstract: Tumour necrosis factor-α (TNF-α) is a double-edged cytokine associated with pathogenesis of inflammatory-related cancers being also able to induce cancer cell death. In the process of tumour development or metastasis, cancer cells can become resistant to TNF-α. In trefoil factor 3 (TFF3) overexpressing colorectal adenocarcinoma cells (HT-29/B6), we observed enhanced resistance against TNF-α/interferon gamma-induced apoptosis. TFF3 is a secreted small peptide that supports intestinal tissue repair but is also i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 49 publications
3
16
0
Order By: Relevance
“…According to the evidence, PRINS acts as an anti-apoptotic lncRNA [48]. In the current study, PRINS lncRNA levels attenuated in both estrogen-dependent and -independent cell lines following CCT137690 exposure.…”
Section: Discussionsupporting
confidence: 55%
“…According to the evidence, PRINS acts as an anti-apoptotic lncRNA [48]. In the current study, PRINS lncRNA levels attenuated in both estrogen-dependent and -independent cell lines following CCT137690 exposure.…”
Section: Discussionsupporting
confidence: 55%
“…Casado et al demonstrated that colorectal cancer cells overexpressing TFF3 showed reduced sensitivity to chemotherapy by being resistant to apoptosis 46 . Hanisch et al reported that TFF3 overexpression enhanced resistance to TNF-α/interferon gamma-induced apoptosis 47 . In the study by Perera et al TFF3 overexpression was associated with reduced sensitivity to ionizing radiation in PCa cells 28 .…”
Section: Discussionmentioning
confidence: 99%
“…11B, we show the close relationship between lncRNA RP11-613D13.8 and miR491-5p. Previous studies regarding miR-491-5p have demonstrated that it played an important role in different cancers, including GC [49,[53][54][55][56], and could also have critical roles in a variety of cellular processes, including cell proliferation, tumor metastasis, tumor invasion, cell apoptosis, and the cell cycle. Sun et al reported that the expression of miR-491-5p was markedly downregulated in GC, which inhibited cell proliferation by disrupting the cell cycle and promoting apoptosis in GC cells via targeting Wnt3a [49].…”
Section: Discussionmentioning
confidence: 99%